2014
DOI: 10.1080/13811118.2013.824826
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Suicidal Ideation and Attempt and Anxiety Symptoms and the Demographic, Psychological, and Social Moderators in Taiwanese Adolescents

Abstract: The objectives of this study were to examine the associations between suicidal ideation and attempt and anxiety symptoms and the moderators in 5,027 Taiwanese adolescents. The associations between suicidal ideation and attempt and anxiety symptoms on the Taiwanese version of the Multidimensional Anxiety Scale for Children (MASC-T) were examined using logistic regression analysis. The moderating effects of demographic (gender and age), psychological (problematic alcohol use, severe depressive symptoms, and low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Research looking at self-esteem as a potential protective factor found that self-esteem buffered against suicidal ideation among students with depressive symptoms but did not do so for those with eating disorder symptoms (Brausch & Decker, 2014). Similarly, self-esteem did not moderate the link between anxiety symptoms and either suicidal ideation or attempts (Yen et al, 2014), and self-image did not buffer the relationship between adopted child status and suicide attempts (Slap, Goodman, & Huang, 2001). Studies focused on self-acceptance as a protective factor also found null results suggesting that this factor does not buffer against suicidal ideation in the presence of depressive symptoms (Lee, 2011) or against suicidal ideation and attempts in the presence of peer victimization in a sample of lesbian, gay, and bisexual teens (Hershberger & D’Augelli, 1995).…”
Section: Resultsmentioning
confidence: 96%
“…Research looking at self-esteem as a potential protective factor found that self-esteem buffered against suicidal ideation among students with depressive symptoms but did not do so for those with eating disorder symptoms (Brausch & Decker, 2014). Similarly, self-esteem did not moderate the link between anxiety symptoms and either suicidal ideation or attempts (Yen et al, 2014), and self-image did not buffer the relationship between adopted child status and suicide attempts (Slap, Goodman, & Huang, 2001). Studies focused on self-acceptance as a protective factor also found null results suggesting that this factor does not buffer against suicidal ideation in the presence of depressive symptoms (Lee, 2011) or against suicidal ideation and attempts in the presence of peer victimization in a sample of lesbian, gay, and bisexual teens (Hershberger & D’Augelli, 1995).…”
Section: Resultsmentioning
confidence: 96%
“…The prevalence of anxiety symptoms among female manufacturing workers of this study may not be seriously high. However, because two recent studies have suggested that the presence of anxiety symptoms is significantly related to the prevalence of suicidal ideation and suicide attempts [ 29 , 30 ]. With suicide being the highest cause of death among Korean women aged between 10 and 39 years old [ 31 ], anxiety symptoms potentially can be important health problem among Korean female workers, especially 10–39 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Major risk factors for suicide can be classified as economic , environmental [e.g., air pollution , second‐hand smoke , or earthquakes ], and individual [e.g., alcohol consumption , drug use , common mental disorders , history of self‐harm , parental psychopathology , or parental separation/divorce in childhood ]. In particular, prior suicide attempt is the single most important risk factor for suicides in the general population .…”
Section: Introductionmentioning
confidence: 99%